Modified B-Lynch suture in post cesarean section uterine atony: Case report - Gamarra, Melvin (2014)
A case of postpartum hemorrhage due to uterine atony is presented where a double compressive type B-Lynch suture with chromic catgut Nº 1 was used because bleeding did not stop with a single suture and chromic catgut Nº 2 was not available.